Malawi strategy support program - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
The International Food Policy Research Institute (IFPRI) launched the Malawi Strategy Support Program (MaSSP) in 2008. The program receives co-funding from the UK Department for International Development (DFID) and the United States Agency for International Development (USAID). The overall objective of MaSSP is to conduct evidence-based research and advise government and development partners on strategic policy options to support agricultural development and economic growth, promote food security, and support broad-based economic growth.